2018
DOI: 10.3892/mmr.2018.8518
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long non‑coding RNA CCAT2 indicates a poor prognosis and promotes proliferation and metastasis in intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (IHCC) is an aggressive cancer with a poor survival rate and is the second most common type of primary cancer of the hepatobiliary system. At present, the molecular mechanisms of IHCC initiation and progression remain unclear. Recent evidence has indicated that long non‑coding RNAs (lncRNAs) serve a crucial role in cancer development; however, the functional role of lncRNAs in IHCC has not been investigated in detail. In the present study, a marked overexpression of lncRNA colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…CRNDE, UCA1, TUG1) was reported to correlate with clinical progression (e.g. tumor grade, lymph node metastasis, TNM stage) and was identified as risk factors for an unfavorable overall survival (OS) in iCCA 16,18,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…CRNDE, UCA1, TUG1) was reported to correlate with clinical progression (e.g. tumor grade, lymph node metastasis, TNM stage) and was identified as risk factors for an unfavorable overall survival (OS) in iCCA 16,18,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments showed that silencing CCAT2 caused cancer suppressive effects through inhibiting cellular proliferation, migration and invasion, accelerating cellular apoptosis, and reversing EMT process Xu, Y. et al, 2018aXu, Y. et al, , 2018b. In addition, enhanced CCAT2 expression was also associated with microvascular invasion, high differentiation grade, and advanced TNM stage confirmed by Bai's research team (Bai et al, 2018). According to these findings, CCAT2 plays a crucial role in CCA progression and shows advantageous characteristics to be an indicator for early diagnosis and prognosis evaluation.…”
Section: Ccat2 and Cholangiocarcinomamentioning
confidence: 75%
“…Only four studies found that lncRNAs were significantly associated with histological grade of CCA, while 13 studies claimed that lncRNAs were significantly correlated with tumor grade of CCA. Interestingly, Table 1 shows that AFAP1-AS1 and CCAT2 expressions were significantly related to vascular invasion 11,28. Additionally, ten studies demonstrated that lncRNAs were significantly associated with lymph node metastasis, while three studies reported that lncRNAs were significantly correlated with distant metastasis.…”
Section: Resultsmentioning
confidence: 99%